A Guide Book for Evaluators - Planning Commission (Planning Commission)
Evaluation is not just an integral part of the planning process but an essential ingredient of development administration. Nevertheless it is a much misunderstood term. As a concept, evaluation is different from project appraisal, which is generally related to the study of the economic feasibility or desirability of making a choice among different investment options. Evaluation is not operational research either, which is being able to experiment and try out an idea and correct the hypothesis. Evaluation studies are also different from pure estimation surveys for they are not merely collection of statistics. They are in fact problem-oriented studies of programmes. The problem areas may relate to policy issues, programme formulation, organisational forms and methods, administrative practices, extension of the technical content of the programme, people's co-operation / attitude etc.
Government of India Regional Evaluation Office Programme Evaluation Organisation Planning Commission Chennai